Acoustic Emission Characteristics and Change the Transformation Entropy after Stress-Induced Martensite Stabilization in Shape Memory Ni53Mn25Ga22 Single Crystal - Tóth, László Zoltán; Daróczi, Lajos; Panchenko, Elena; Chumlyakov, Yuri; Beke, Dezső László (Materials, 2020)
Measurements have been carried out to compare stress-induced martensite stabilization aged (SIM-aged) and as grown shape memory Ni53Mn25Ga22 single crystals with the means of simultaneous differential scanning calorimetry (DSC) and acoustic emission (AE). Contrary to expectations, the position of the hysteresis practically did not change, whilst the width of the hysteresis increased, and the forward and reverse transitions became sharper in the SIM-aged sample. The energy distributions of acoustic hits showed regular power law behaviour and the energy exponents were slightly different for heating and cooling; this asymmetry had different signs for the SIM-aged and as grown samples. During heating, in accordance with the sharper transitions observed in the DSC runs, two well-marked jumps could be seen on the plot of cumulative number of the acoustic emission events. Therefore, these were attributed to high sudden jumps in the phase transition during heating observed in the DSC. The effect of the SIM-aging on the transformation entropy was also investigated and it was found that it was about 36% less in the case of the SIM-aged sample.